FAKTOR – FAKTOR PENYEBAB KURANGNYA MINAT MAHASISWA BERWIRAUSAHA (Studi Kasus : Mahasiswa Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Katolik Santo Thomas) - Simanihuruk, Peran; Simanjuntak, Markus Doddy (Jurnal Manajemen dan Bisnis, 2024)
This study aims to investigate the factors causing a lack of interest among students in entrepreneurship in the Management Program of the Faculty of Economics and Business at the Catholic University of Santo Thomas. Data collection methods involved questionnaires and interviews with the participation of 125 students, and data analysis techniques utilized factor analysis.The research findings reveal that the primary factors influencing the lack of entrepreneurial interest among students can be categorized into seven main groups. The first group includes the fear of starting, reluctance to face risks, fear of challenges, lack of self-reliance, lack of experience, and insufficient family support. The second group involves the fear of failure, parental disapproval, and dependence on parents. The third group comprises the inability to identify opportunities, lack of talent, the desire to become an employee, and the absence of capital. The fourth group includes a lack of business management skills, low self-confidence, and social stigma. The fifth group encompasses a lack of perseverance, innovation, creativity, and mentorship. The sixth group involves difficulties in sales, time management challenges, and a lack of collaboration. The seventh group encompasses the fear of stepping out of the comfort zone and past experiences of failure.To enhance students' interest in entrepreneurship, it is recommended to integrate entrepreneurship courses into the curriculum, organize structured entrepreneurship programs or workshops, provide training and mentoring by successful business practitioners or alumni, foster collaboration with local business actors, develop soft skills, organize extracurricular activities, offer financial support, establish business incubators on campus, and provide access to facilities and infrastructure supporting business endeavors.